Central administration of human opiorphin alleviates dextran sodium sulfate-induced colitis in mice through activation of the endogenous opioid system - Luo, Pan; Li, Xuelin; Gao, Yuan; Chen, Zhengjun; Zhang, Quanwei; Wang, Zhimin; Tian, Xiaozhu (Frontiers in Pharmacology, 2022)
Opioid system plays a crucial role in maintaining gastrointestinal homeostasis. Endogenous opioid peptide enkephalins have anti-inflammatory effect and participate in the treatment of inflammatory bowel diseases (IBDs). Here, we investigated the effect of natural enkephalinase inhibitor human opiorphin (HO) on dextran sodium sulfate (DSS)-induced colitis in mice. Our results showed that central administration of HO attenuated DSS-induced colitis, as indicated by the reduction of disease activity index (DAI) scores, macroscopic scores, histological scores and myeloperoxidase (MPO) activity. Moreover, HO alleviated DSS-induced inflammation by decreasing inflammatory cytokines TNF-α, IL-6 and IL-1β, and increasing anti-inflammatory cytokine IL-10 in both serum and colon tissue in DSS-treated mice. The potential anti-inflammatory effect of HO at dose of 40μg/kg was observed as evidenced by decrease in nuclear factor κB (NF-κB) p65, toll-like receptor-4 (TLR-4), iNOS and COX-2. HO also improved intestinal barrier function by enhancing the expression of tight junction proteins. Furthermore, HO treatment significantly inhibited activities of neutral endopeptidase (NEP) and aminopeptidase N (APN), elevated serum enkephalins concentrations, and increased expressions of mu and delta opioid receptor. In addition, pretreatment with opioid receptor antagonist naloxone hydrochloride (NH) compromised the protective effect of HO and aggravated colitis symptoms, as indicated by inhibited anti-inflammatory effects, disrupted intestinal barrier function, and decreased opioid receptor activity. In conclusion, these data indicate that HO protects against DSS-induced colitis by inhibiting TLR4/NF-κB pathway activation and improving intestinal barrier function through activation of endogenous opioid system. Therefore, targeting opioid system with peptidase inhibitors intervention would be a novel strategy in the therapy of IBD.